2022
DOI: 10.1039/d2sc03723h
|View full text |Cite
|
Sign up to set email alerts
|

Support stabilized PtCu single-atom alloys for propane dehydrogenation

Abstract: PtCu single-atom alloy (SAA) opens an extensive prospect for heterogeneous catalytic processes. However, as the host of SAA, Cu suffers from severe sintering at elevated temperature, resulting in poor stability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…30,31 The peak appearing at 2048 cm −1 was ascribed to the unsaturated coordinated metallic Pt sites. 11,12,23,25,32 During the desorption process, strongly adsorbed CO still remained on the Pt/SiO 2 catalyst (Fig. S3 †).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 The peak appearing at 2048 cm −1 was ascribed to the unsaturated coordinated metallic Pt sites. 11,12,23,25,32 During the desorption process, strongly adsorbed CO still remained on the Pt/SiO 2 catalyst (Fig. S3 †).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…9 Alloying is a common strategy for isolating Pt to avoid side reactions. Metallic elements with low electronegativity, such as Ga, [10][11][12][13] In, [14][15][16] Sn [17][18][19][20][21][22] and Cu, [23][24][25] are widely used to form alloys with Pt. Electrons can be transferred from these electronegative metals to Pt, leading to the formation of electron-rich states of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…By using in situ aberration-corrected transmission electron microscopy, Liu et al found that metal nanoparticles with smaller contact angles have stronger interfacial interactions with the substrates. 19 The difference of interfacial interaction can also be studied by various spectroscopic techniques, such as X-ray photoelectron spectroscopy (XPS), 20,21 X-ray absorption spectroscopy, 20 and in situ diffuse reflectance infrared spectroscopy. 21 Herein, we appeal to the surface-sensitive technique of scanning tunneling microscope (STM) to investigate the oxide−metal interaction.…”
mentioning
confidence: 99%
“…19 The difference of interfacial interaction can also be studied by various spectroscopic techniques, such as X-ray photoelectron spectroscopy (XPS), 20,21 X-ray absorption spectroscopy, 20 and in situ diffuse reflectance infrared spectroscopy. 21 Herein, we appeal to the surface-sensitive technique of scanning tunneling microscope (STM) to investigate the oxide−metal interaction. The atomic structures and local electronic states of supported nanostructures can be obtained by STM topography and spectroscopy, respectively.…”
mentioning
confidence: 99%
“…Since the concept of the single-atom alloy was first proposed, SAA catalysts have been widely used in various chemical reactions, including hydrogenation of unsaturated hydrocarbons, ,,, dehydrogenation of hydrocarbons, , hydrogenolysis of biomass molecules, , and electrochemical reduction reactions, , to name a few. These reactions on SAA catalysts are almost carried out under reducing conditions, whereas oxidation reactions are usually promoted by corresponding single atoms deposited on oxide surfaces .…”
mentioning
confidence: 99%